Early vs. late worsening heart failure during acute heart failure hospitalization: insights from the PROTECT trial. (17th June 2015) - Mentz, Robert J.; Metra, Marco; Cotter, Gad; Milo, Olga; McKendry, Colleen; Chiswell, Karen; Davison, Beth A.; Cleland, John G.F.; Bloomfield, Daniel M.; Dittrich, Howard C.; Fiuzat, Mona; Ponikowski, Piotr; et al.
<x xml:space="preserve">Abstract</x> Background Worsening heart failure (WHF) symptoms despite initial therapy during admission for acute heart failure (AHF) is associated with worse outcomes. The association between the time of the WHF event and the intensity of WHF therapy with outcomes is unknown. Methods and results In the PROTECT trial of 2033 AHF patients, we investigated the association between time of occurrence of WHF and intensity of therapy, with subsequent outcomes. WHF was defined by standardized, physician‐determined assessment. Early WHF was defined as occurring on days 2–3 and late on days 4–7. Low intensity included restarting/increasing diuretics or vasodilators and high intensity included initiation of inotropes, vasopressors, inodilators, or mechanical support. Outcomes were death or cardiovascular/renal hospitalization over 60 days and death over 180 days. Of the 1879 patients with complete follow‐up after day 7, 12.7% (n = 238) experienced WHF: 47.9% early and 52.1% late. Treatment intensity was low in 72.3% and high in 24.8% (2.9% missing). After adjusting for baseline predictors of outcome, WHF was associated with a trend toward increased 60‐day death or cardiovascular/renal hospitalization [hazard ratio (HR) 1.26; 95% confidence interval (CI) 0.99–1.60; P = 0.063] and increased 180‐day death (HR 1.77; 95% CI 1.33–2.34; P < 0.001). There was no evidence of a differential association between the time of occurrence of WHF and outcomes. High‐intensity therapy was not significantly associated with increased event rates (180‐day mortality: HR 1.44; 95% CI 0.80–2.59 vs. low). Conclusions Inhospital WHF was associated with increased 180‐day death. The time of occurrence and intensity of WHF therapy may provide less prognostic information than whether or not WHF occurred.